THE EFFECTS OF THE INTRODUCTION OF THE TV SCREEN IN EVERYDAY AND PERSONAL SPACE - Sergey L. Grigoryev (Russian Studies in Culture and Society)
Purpose. The purpose of this study is to identify and fix the nature of the changes associated with the emergence and subsequent change in the role of television within the sociocultural universe of modern man. An analysis of its features, characteristics and factors that are currently causing the most significant changes within this sphere, which actually creates its own “second reality”.